Excitation rates of heavy quarks - García Canal, Carlos Alberto (1985)
We obtain the production rates for c, b, and t quarks in deep-inelastic neutrino- (antineutrino-) nucleon interactions, in the standard six-quark model with left-handed couplings. The results are obtained with the most recent mixing parameters and we include a comparison between quark parametrizations. The excitations are calculated separately for each flavor, allowing the understanding of the role of threshold effects when considered through different rescaling variables.